Requirement of PML SUMO Interacting Motif for RNF4- or Arsenic Trioxide-Induced Degradation of Nuclear PML Isoforms - Maroui, Mohamed Ali; Kheddache-Atmane, Sabrina; El Asmi, Faten; Dianoux, Laurent; Aubry, Muriel; Chelbi-Alix, Mounira K. (PLOS ONE, 2012)
PML, the organizer of nuclear bodies (NBs), is expressed in several isoforms designated PMLI to VII which differ in their C-terminal region due to alternative splicing of a single gene. This variability is important for the function of the different PML isoforms. PML NB formation requires the covalent linkage of SUMO to PML. Arsenic trioxide (As2O3) enhances PML SUMOylation leading to an increase in PML NB size and promotes its interaction with RNF4, a poly-SUMO-dependent ubiquitin E3 ligase responsible for proteasome-mediated PML degradation. Furthermore, the presence of a bona fide SUMO Interacting Motif (SIM) within the C-terminal region of PML seems to be required for recruitment of other SUMOylated proteins within PML NBs. This motif is present in all PML isoforms, except in the nuclear PMLVI and in the cytoplasmic PMLVII. Using a bioluminescence resonance energy transfer (BRET) assay in living cells, we found that As2O3 enhanced the SUMOylation and interaction with RNF4 of nuclear PML isoforms (I to VI). In addition, among the nuclear PML isoforms, only the one lacking the SIM sequence, PMLVI, was resistant to As2O3-induced PML degradation. Similarly, mutation of the SIM in PMLIII abrogated its sensitivity to As2O3-induced degradation. PMLVI and PMLIII-SIM mutant still interacted with RNF4. However, their resistance to the degradation process was due to their inability to be polyubiquitinated and to recruit efficiently the 20S core and the β regulatory subunit of the 11S complex of the proteasome in PML NBs. Such resistance of PMLVI to As2O3-induced degradation was alleviated by overexpression of RNF4. Our results demonstrate that the SIM of PML is dispensable for PML SUMOylation and interaction with RNF4 but is required for efficient PML ubiquitination, recruitment of proteasome components within NBs and proteasome-dependent degradation of PML in response to As2O3.